EVALUATION OF THE MBKM INTERNSHIP PROGRAM ON THE LEVEL OF STUDENT SATISFACTION IN ACHIEVING LEARNING OBJECTIVES - Sulaowady, Patricia; Limputra, Samuel Elmer; Maichal, Maichal (Universitas Ciputra Surabaya, 2024)
This study aims to evaluate the success of the Merdeka Belajar Kampus Merdeka (MBKM) Internship Program for the period of September 2023 to January 2024. This research employs a descriptive statistical approach, where data is collected through the distribution of specifically designed questionnaires to assess various aspects of participants' experiences. A quantitative descriptive method will be used as the basis for objectively and measurably addressing the research questions. Data collection is carried out through the distribution of questionnaires with closed-ended statements. The results of this study are expected to provide a deeper understanding of the impact of the MBKM program on students, particularly in terms of individual character development and adaptation to the MBKM environment. Additionally, this research aims to identify the level of support provided by educational institutions to program participants and how this support influences the participants' success and experience. Thus, the findings of this research are anticipated to contribute meaningfully to improving the quality of the MBKM program implementation in the future and to offer recommendations for more effective educational policies. Based on the results, the MBKM internship program generally has a positive impact on student satisfaction, particularly in the de